(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
أجريت هذه الدراسة على الصدوع الظاهرة ضمن الصخور الكريتاسية، في الجزء الشرقي والمركزي من رقعة الحفة في السلسلة الساحلية – شمال غرب سورية. تهدف هذه الدراسة إلى إعادة بناء الإجهادات القديمة منذ الأبتي حتى الماستريختي، من خلال تحليل معطيات الصدوع التكسّرية بطريقة INVD من برنامج Angelier، ومن ثم وضع هذا التطور وتفسيره ضمن إطاره الجيودينامي العام. تم تعيين طورين تكتونيين إقليميين: الأول: طور شدّي ذو اتجاه شمال غرب – جنوب شرق في توضعات الألبي – السينوماني، والذي تم تحديده بصدوع عادية مرافقة للترسيب اتجاهها شمال شرق – جنوب غرب. إن هذا الطور مرتبط مع الانفتاح النشيط للنيوتيتس في شرق المتوسط. الثاني: طور شدّي ذو اتجاه شمال شرق – جنوب غرب في توضعات التوروني، والذي تمّ تحديده عن طريق صدوع عادية مرافقة للترسيب اتجاهها شمال غرب – جنوب شرق. يرتبط هذا الطور مع الطور الشدّي الإقليمي في شمال الصفيحة العربية، المترافق مع انهدامات إقليمية مثل انهدامي الفرات في سورية والأزرق في الأردن. This study deals with revealed faults on Cretaceous sediments in eastern and central parts of Alhaffa area – Coastal Range - NW of Syria. This study’s aim is to reconstitute the paleo-stress since Aptian to Maastrichtian, which was based on INVD method from Angelier`s program to analyses fault slip data and replace it in its general geodynamic frame. Tow regional tectonic events were determined: 1- NW-SE extension in Albian - Cenomanian deposits, which was determined by NE-SW syndepositional normal faults. This event is related to the reactivation of opening of Neo-Tethys in Eastern Mediterranean, 2- NE-SW extension in Turonian deposits, which were determined by NW-SE syndepositional normal faults. This event is related to a regional extensional event in the northern Arabian plate which is associated with regional rifting as Euphrates (Syria) and Azraq (Jordan).